THE ROLE OF ISLAMIC CAPITAL MARKET FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) THROUGH SYNERGY OF MUTUAL FUND AND VENTURE CAPITAL INSTITUTION - Sanrego, Yulizar D. (Bank Indonesia, 2017)
It is worldly known that one of the main obstacles which is often faced by the micro, small, and medium enterprises (MSMEs) practitioners is the ability to access sources of funding. At the time where the absorption of banking credit to MSMEs is still very limited, the role of sharia capital market is considered as an alternative to support this limitation. Expanding the role of sharia capital market finds it moment when Indonesia Finance Service Authority (FSA) issued regulations that provide space for the capital market to also active in real sector businesses. In accordance with the FSA Rules N0.37/2014, mutual fund (unit trust) in the form of Collective Investment Contract (CIC) - Limited Investment/ Participation Fund (LPF) has the objective to pave the way for mutual fund investors to make direct investments in real investments. The proposed model that might be realized to smoothen the intermediary role of sharia capital market to the development of MSMEs is through the hybrid model that might linking mutual fund/investment manager and corporate, particularly venture capital. Using Analytical Network Process (ANP) approach this paper indicates that with the value of rater agreement 1.0, the research found that there are four main cluster problems which become an obstacle the proposed model, namely: (a) the reputation of mutual fund/investment manager; (b) investment grade rating of corporate (venture capital); (c) risk appetiate of investor as shahib al-mal; and (d) government regulation. Policy recommendation that might become solution, according to the value of rater agreement 1.0 is sequentially as follow, namely: (a) fully support from government; especially for a relatively new mutual fund with no experience in the capital markets industry; (b) Corporate (venture capital) should be able to offer Islamic Microfinance Finance Institutions (IMFIs) and MSMEs that have good business feasibility to the mutual fund/investment manager as well as investor; (c) the government should be able to guarantee legal certainty in the context of protection, including advocacy for investors; and last but not least (d) There is an extremely hope that investors could change their investment behavior paradigm, from risk averse to risk taker.